Service Quality of Electronic Medical Records Using DeLone–McLean Model - Grafirat Wengkang; Wahyu Wijaya Widiyanto (Universitas Duta Bangsa Surakarta, 2026)
Background: Indonesia requires healthcare facilities to implement electronic medical records (EMRs), yet integration progress and implementation capacity remain uneven. Evidence from primary healthcare is especially limited because most evaluations have been undertaken in hospitals. This study examined whether system quality, information quality, service quality, and user satisfaction were associated with perceived health service quality among users of the EMR at Opi Palembang Primary Health Center using an adapted DeLone-McLean Information Systems Success Model. Methods: A quantitative cross-sectional study involved all 52 eligible healthcare professionals and administrative staff who had used the EMR for at least three months. Data were collected using a structured five-point Likert questionnaire. Descriptive statistics, Pearson correlations, and multiple linear regression were used to examine the relationships between the four information-system success dimensions and perceived health service quality. Results: All four dimensions were positively correlated with perceived health service quality: user satisfaction (r=0.65, p<0.001), system quality (r=0.62, p<0.001), information quality (r=0.58, p=0.001), and service quality (r=0.49, p=0.003). The regression model explained 68% of the observed variance (R²=0.68). User satisfaction had the largest observed unstandardized coefficient (B=0.287, p=0.002), followed by system quality, information quality, and service quality. Conclusion: The adapted DeLone-McLean dimensions were consistently associated with users’ perceptions of service quality. The results support improvements in usability, information accuracy and timeliness, technical support, and workflow fit. Because the design was cross-sectional and based on perceptions from one facility, the findings should not be interpreted as evidence that the EMR caused objective improvements in care